2016
DOI: 10.1002/mbo3.420
|View full text |Cite
|
Sign up to set email alerts
|

A family of genus‐specific RNAs in tandem with DNA‐binding proteins control expression of the badA major virulence factor gene in Bartonella henselae

Abstract: Bartonella henselae is a gram‐negative zoonotic bacterium that causes infections in humans including endocarditis and bacillary angiomatosis. B. henselae has been shown to grow as large aggregates and form biofilms in vitro. The aggregative growth and the angiogenic host response requires the trimeric autotransporter adhesin BadA. We examined the transcriptome of the Houston‐1 strain of B. henselae using RNA‐seq revealing nine novel, highly‐expressed intergenic transcripts (Bartonella regulatory transcript, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Not surprisingly, we have shown that BadA plays an important role in biofilm formation by B. henselae, as a badA deletion mutant has an impaired ability to form biofilms (Fig. 8) (75). When our laboratory constructed nonpolar deletion mutants of the badA gene in both the Houston-1 type strain and the Marseille strain of B. henselae, they were shown to have a reduced ability to form biofilms.…”
Section: Growth In Biofilmsmentioning
confidence: 81%
See 4 more Smart Citations
“…Not surprisingly, we have shown that BadA plays an important role in biofilm formation by B. henselae, as a badA deletion mutant has an impaired ability to form biofilms (Fig. 8) (75). When our laboratory constructed nonpolar deletion mutants of the badA gene in both the Houston-1 type strain and the Marseille strain of B. henselae, they were shown to have a reduced ability to form biofilms.…”
Section: Growth In Biofilmsmentioning
confidence: 81%
“…Expression of TAA genes is also highly variable among different species, within strains of the same species (72), and even under different conditions (74). The expression of TAA genes correlates with autoaggregation and has also been recently shown to play an important role in biofilm formation by B. henselae (75). It is well known that these autoaggregative properties are more apparent in recent low-passage-number isolates.…”
Section: Microbiology Of the Genus Bartonella Growth Propertiesmentioning
confidence: 99%
See 3 more Smart Citations